تجربة صناعة التكافل في تايلاند: منتجات موانج تهاي للتكافل أنموذجا = The experience of takaful industry in Thailand: a case study of Muang Thai Takaful - Laeba, Muhammad; Hama, Zakariya (Islamic Yala University, 2013)
The research aims to shed light on the experience of Takaful Industry in Thailand in terms of its establishment, development, and the legislations governing it. The study will also discuss the sample of products of Muang Thai Takaful which is being provided by the two of Muang Thai companies i.e Muang Thai insurance and Muang Thai life assurance from the shariah perspective, by looking at the contract between the company - as an agent of the subscribers- and the participant, as well as the activities undertaken by the company to invest its funds. The research have adopted the inductive, analytical and practical methods, while for collection data, they have depended on a number of sources and resources as well as some contemporary studies. There are also some data which have been collected during an indepth interview with the relevant personality. The Takaful Products provided through Islamic Windows at Conventional Takaful Company including Muang Thai insurance and Muang Thai life assurance, by engineering a number of legitimate contracts containing of agency contract, interdependence contract, donation contract, as well as the guarantor contract need to be developed from both legal and shariah perspectives as concluded by the researchers. There is also strong need for the establishment of an independent Islamic Insurance or Takaful Company in Thailand.